2020
DOI: 10.1186/s12889-020-09632-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring attitudes of adolescents and caregivers towards community-based delivery of the HPV vaccine: a qualitative study

Abstract: Background Human Papillomavirus (HPV) vaccination among adolescents is an important strategy to prevent cervical and other cancers in adulthood. However, uptake remains far below the Healthy People 2020 targets for the US. Given the barriers to population-level vaccination policies and challenges to incorporating additional action items during clinical visits, we sought to explore alternative delivery mechanisms, specifically delivery of the vaccine in community settings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…Similar to our studies 33,34 , parents have recommended workshops in a school setting given the accessibility and confidence. Since the HPV vaccine is a school requirement, it is of the utmost importance that the schools have trained school personnel and, likewise, integrate parents and students in the process to enhance the engagement 35 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar to our studies 33,34 , parents have recommended workshops in a school setting given the accessibility and confidence. Since the HPV vaccine is a school requirement, it is of the utmost importance that the schools have trained school personnel and, likewise, integrate parents and students in the process to enhance the engagement 35 .…”
Section: Discussionsupporting
confidence: 52%
“…Most of the barriers discussed in our study are modifiable with the implementation of educational programs, health communication strategies across agencies responsible for the implementation, public acceptability, and political acceptability to support this policy. 33,[38][39][40] According to an unpublished preliminary results using data of 2010 through 2019 provided by the Puerto Rico Immunization Registry from our research team, a subtle but significant increase in HPV vaccination (initiation, not completion against HPV) has been observed after implementing the requirement. However, at this time, we are unaware if the COVID-19 pandemic has made an impact on parental perception to the school required vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of communication between the parents and guardians with the school and health providers was the main barrier to the HPV vaccine school entry policy. Similar to our studies [ 21 , 30 , 31 ] , parents have recommended workshops in a school setting given the accessibility. Having trained school personnel and integrate parents and students, the school could improve the engagement with the HPV vaccine policy [ 32 ].…”
Section: Discussionmentioning
confidence: 63%
“…We conducted this study in a timely opportunity to understand the parental perceptions regarding the implementation of this recent HPV vaccine requirement. Most of the barriers identified could be modifiable addressing with targeted educational programs with parents, school staff and providers, health communication strategies across agencies responsible for the implementation, public acceptability, and political acceptability to support this policy [ 29 , 31 , 45 ]. According to unpublished preliminary results using data of 2010 through 2019 provided by the Puerto Rico Immunization Registry and our research team, an increase of 54% was observed in HPV vaccination initiation rate (not completion) for 11–12 years old children after implementing the requirement [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…School-based vaccination has proven a successful strategy to achieve high HPV vaccine coverage in many countries, 17 , 18 and was previously indicated as the most acceptable approach by adolescents in the United States. 19 However, our study participants consistently argued that community-based vaccination delivery would be preferable in the local setting, because it may improve accessibility and promote vaccination uptake among those who do not trust healthcare facilities. In November 2019, Pakistan introduced typhoid conjugate vaccine administration through schools and hospitals.…”
Section: Discussionmentioning
confidence: 87%